The Determinants of Earnings Management in Indonesian Public Companies - Leonardo Davidsi Sipayung; Fitriana; Eureka Try Zarazwanty R Laega (Fakultas Ilmu Sosial dan Hukum, 2026)
Indonesia is the biggest economy in the southeast Asia. This paper investigates the earnings management behavior of Indonesian public firms. The earnings management activities have been divided into three parts. Namely, accrual earnings management, real earnings management and fraud detection. Our findings indicate that earnings management activities are common for Indonesian firms. Firm size and asset growth have significant relationship associated, with various directions, with both accrual earnings management and real management activities for Indonesian firms. We also find that firm size, asset growth, ROE, and debt ratio consistently have significant relationship to real earnings management. In predicting the possibility of Indonesian firm to commit financial fraud, we find that manipulating gross margin, sales growth, depreciations and expenses related to sales and general administration is common seen from fraudulent firms in Indonesia.